Nutrient production and micronutrient gaps: Evidence from an agriculture-nutrition randomized control trial - Dillon, Andrew; Arsenault, Joanne E.; Olney, Deanna K. (Agricultural and Applied Economics Association, 2019)
Integrated agriculture nutrition programs can increase the quantity and quality of nutritious foods through multiple pathways. Increased household production increases the availability of own produced food for consumption, as well as income for food purchases. Increased knowledge of nutrition introduced through a behavior change communication strategy can change food preferences and shift purchasing decisions towards nutritious foods. In a randomized control trial, we demonstrate that an integrated agriculture‐nutrition program in Burkina Faso improved the quality of diets by reducing household macro and micronutrient consumption gaps. We estimate production and consumption nutrient gaps for households in our sample by comparing reported consumption or production of nutrients relative to recommended daily allowances for households. Differences between actual nutrient consumption and production values and the recommended daily allowances provide an estimate of the nutrient gaps (surplus or deficit) within the household. We find that the integrated agriculture‐nutrition program reduced consumption nutrient gaps in treatment households. We also investigate whether the production or nutrition knowledge pathways explain the consumption nutrient gap treatment effects. Though crop choice led to a diversified household production of nutritious foods in treatment villages on the extensive production margin, increased household production of nutrients does not explain the improvements in diet quality due to limited treatment effects for the estimated production nutrient gaps at the intensive production margin. Consumption expenditures in treatment villages did increase purchases of nutritious foods, suggesting that the behavior change communication strategy is effective at not only increasing nutrition knowledge, but also in affecting consumer preferences.